Vietnam (Herts : Screen Entertainment, 1992)
From the killing fields of Vietnam to the battlefields of the streets at home, the war is a re-occuring nightmare for Goddards, whose only son Phil is drafted.'Vietman' brutally and frankly recounts Phil's four shattering years atwar
Keywords: Vietnamese Conflict, 1961 -- 1975 -- Motion pictures and the conflict; War stories -- Drama